THE ROLE OF MEDICATION LITERACY IN THE TREATMENT OF HYPERTENSIVE PATIENTS: A REVIEW - Okti Ratna Mafruhah; Vita Widyasari (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Hypertension, or high blood pressure, has become a major contributor to cardiovascular disease globally. Its prevalence continues to increase, necessitating intensive healthcare efforts. Medication literacy, or the skill of understanding and applying medication information, is crucial for chronic patients, including those with hypertension. However, there has been limited research on this topic, highlighting the need for a literature review of the levels and roles of literacy in the therapy of hypertensive patients. This study used a narrative review approach to analyze the findings of articles on medication literacy in hypertensive patients. This study employs a narrative review approach to analyze findings from various journals. The data were derived from articles focusing on medication literacy in hypertensive patients, identified through literature searches on PubMed from 2013 to 2023. The selected articles were published in international journals, have a full text, can provide data on the role of medication literacy in hypertensive patients, and use quantitative, qualitative, or mixed-methods research designs.Two studies included in the review originated from China. Both articles reported low literacy levels among hypertensive patients. Factors, such as education and income, can also influence literacy. These findings underscore the importance of improving medication literacy in hypertension management, emphasizing the need for better education and more effective development strategies. Both articles also emphasized the significance of medication literacy in the context of hypertension management; that is, they highlighted the need for improved medication literacy and provided evidence of the positive impact of medication literacy on blood pressure control...